Deliverable 1.5 Report on stakeholder interaction in year 2 and 3 - Buch, Erik; Sandven, Stein; Danielsen, Finn; Iversen, Lisbeth; Poulsen, Michael Køie; Ottersen, Geir (Zenodo, 2019)
An overview of information, products and services requested by users representing primarily the private commercial sector has been collected via INTAROS user survey supplemented with results from similar surveys performed by other projects and organisations together with information obtained by INTAROS consortium members in dialog with relevant user at meetings, workshops and conferences. Most important products: • Pre-operational phase o Model projections on the long-term (years) development o Risk assessment associated with safe navigation, deployment and recovery of gear, seabed mining, hydrocarbon extraction etc o Statistics and analysis based on existing data • Operational Phase o Operational Services – real-time observations and/or short-term forecasts (5-10 days) o Ship routing o Risk assessment Information on sea Ice (concentration, ice edge, drift thickness) and iceberg are central in the required product portfolio; but the surveys additionally revealed requests for meteorological parameters (pressure, wind, temperature, visibility, precipitation, humidity, icing) and oceanographic parameters (temperature, currents and waves, salinity, oxygen and chlorophyll). The users have very strong demands to resolution in space and time, quality and timeliness of the products they receive: • a horizontal resolution of down to 100 m especially for special ice products was articulated. • Updating frequency for the information are generally requested to be less than one day preferably down to a few hours. • Quality shall regularly be documented and the inclusion of uncertainty information as an integral part of the product is desirable • For operational services it is important that every product update is available in near real-time. For other types of products up to a few days are regarded as timely delivery. • For model forecast the most important forecasting period is the next 2-3 days for operational purposes, while longer forecasting periods 7-10 days are valuable for more long-term planning purposes. Due to ...